Ecstasy induced acute myocardial infarction. Issue 6 (1st June 2001) - Qasim, A; Townend, J; Davies, M K
Abstract : A 23 year old man presented with a clinical history and ECG compatible with acute myocardial infarction, having taken a single tablet of ecstasy (3, 4-methylenedioxymetamphetamine) 18 hours previously. He was treated with aspirin and thrombolytic therapy; however, cardiac catheterisation showed angiographically normal coronary arteries and left ventricular function. Sympathomimetic drugs are freely available and widely abused in Britain, but there is little evidence of the mechanisms or management of cardiac complications. In such cases the use of standard treatment for acute myocardial infarction is recommended with agents such as glyceryl trinitrate and phentolamine to reduce coronary artery spasm. Early coronary angiography may help to determine the relative contribution of spasm, thrombus, and underlying atherosclerotic disease.